The Influence Of Digital Marketing And Electronic Word Of Mouth On Purchasing Decisions (Survey of Lestari Product UMKM Consumers) - Andriyanto, Muhammad Adi; Fitriadi, Budhi Wahyu; Oktaviani, Nita Fauziah (Universitas Dehasen Bengkulu, 2024)
This research aims to determine the influence of Digital Marketing and Electronic Word of Mouth on Survey Purchasing Decisions for Sustainable Product MSME Consumers. This research method is a quantitative approach with a causal descriptive survey method, the population in this study is not known for certain and a sample of 100 respondents was taken. The analytical tool used in this research is multiple regression using SPSS version 25. The research results show that Digital Marketing and Electronic Word of Mouth simultaneously have a significant effect on Purchasing Decisions. Digital Marketing partially has a significant effect on purchasing decisions, Electronic Word Of Mouth partially has a significant effect on purchasing decisions.